Identifying rent-sharing using firms' energy input mix - Matthias Mertens; Steffen Müller; Georg Neuschäffer (Halle Institute for Economic Research (IWH), 2022)
We present causal evidence on the rent-sharing elasticity of German manufacturing firms. We develop a new firm-level Bartik instrument for firm rents that combines the firms' predetermined energy input mix with national energy carrier price changes. Reduced-form evidence shows that higher energy prices depress wages. Instrumental variable estimation yields a rent-sharing elasticity of approximately 0.20. Rent-sharing induced by energy price variation is asymmetric and driven by energy price increases, implying that workers do not benefit from energy price reductions but are harmed by price increases. The rent-sharing elasticity is substantially larger in small (0.26) than in large (0.17) firms.
urn:nbn:de:gbv:3:2-911332
Keywords: C26; J30; P18; 330; Bartik instrument; energy prices; rent-sharing; wage inequality